EFFECT OF ISLAMIC FINANCIAL SYSTEM STABILITY ON ECONOMIC PERFORMANCE IN INDONESIA - Siong Hook Law; Masagus M. Ridhwan (Bank Indonesia, 2022)
This study constructs a financial stability index for the Islamic financial system of Indonesia using the dynamic factor model and then links it to economic performance employing a nonlinear autoregressive distributed lag (NARDL) model. The financial stability index constructed from a broad range of macrofinancial variables captures well the 2008-2009 global financial crisis and the 2020-2021 COVID 19 pandemic crisis periods. The most significant results suggest that positive and negative shocks in Islamic financial stability in the long run increase and decrease economic performance, respectively. The quantile regression results also demonstrate that Islamic financial stability is statistically significant throughout all quantiles in promoting economic performance, although it plays a greater role at lower quantiles and diminishes when the economic performance is at a high level. Our results highlight that the stability of the Islamic financial system deepening would positively enhance economic performance.